2019
DOI: 10.1186/s12884-019-2488-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vulvovaginal candidiasis, bacterial vaginosis and trichomoniasis in pregnant women attending antenatal clinic in the middle belt of Ghana

Abstract: Background Vaginal infections usually caused by Candida sp, organisms responsible for bacterial vaginosis and Trichomonas vaginalis are associated with considerable discomfort and adverse outcomes during pregnancy and child birth. The study determined the prevalence of vulvovaginal candidiasis (VVC), bacterial vaginosis (BV) and trichomoniasis (TV) in pregnant women attending antenatal clinic at the Kintampo Municipal Hospital. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
5
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 50 publications
12
35
5
8
Order By: Relevance
“…The prevalence rates we found are slightly higher than those reported by previous studies [13,16,17,19]. However, our data were more or less consistent with the frequencies reported by previous studies conducted in India (36%), Uganda (45.4%), and in the middle belt of Ghana (36.5%) [15,38,39]. Notably, the highest frequency of VVC in our study was recorded in pregnant women in their third trimester (57.4%).…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence rates we found are slightly higher than those reported by previous studies [13,16,17,19]. However, our data were more or less consistent with the frequencies reported by previous studies conducted in India (36%), Uganda (45.4%), and in the middle belt of Ghana (36.5%) [15,38,39]. Notably, the highest frequency of VVC in our study was recorded in pregnant women in their third trimester (57.4%).…”
Section: Discussionsupporting
confidence: 87%
“…Different strains of Candida have been isolated from 21% of women who reported abnormal vaginal discharge at the Gynecological Department of the Komfo Anokye Teaching Hospital (KATH) in Kumasi, Ghana (Feglo and Narkwa 2012). Similar results were con rmed by Konadu et al (2019), who reported prevalence of 36.5% of VVC among pregnant women attending antenatal clinic in the middle belt of Ghana.…”
Section: Introductionmentioning
confidence: 58%
“…Furthermore, recurrent vulvovaginal candidiasis defined as at least four repeating candida infections per year is an emerging global clinical problem that affects 138 million women every year [ 142 , 143 ]. Among all of the vulvovaginal candidiasis treatment strategies local drug administration has the most advantageous safety and efficiency profile as it reduces the risk of side effects, especially in extreme caution conditions, e.g., pregnancy [ 144 , 145 ].…”
Section: Emulsion-based Vaginal Dosage Forms With Drugs From Different Therapeutic Groups—biological Evaluation and Examples Of In Vivo Amentioning
confidence: 99%